Indeks Kualiti Air (IKA) Sg. Selangor pasca pembinaan Empangan Sg. Selangor - Mokhtar Jaafar,; Asmah Ahmad,; Zaini Sakawi,; Maimon Abdullah,; Norela Sulaiman,; Normukhnun Mokhtar, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
A study of Sg. Selangor Water Quality Index (WQI) after the construction of Sg. Selangor Dam has been conducted in 2008. The results show that the overall WQI of Sg. Selangor may be categorized as Class III. However, the downstream part of Sg. Selangor could be categorized as Class IV. With concentrations of BOD and NH4 being the highest reported among the WQI parameters, it can be concluded that Sg. Selangor is in need of an intensive treatment to stabilise its water quality. The degradation of the river water quality could be linked to recent changes in land use within the Sg. Selangor Basin, especially with regard to agricultural activities, urban development and housing schemes. A continuous monitoring process should be implemented to ensure that Sg. Selangor can sustain the various socio-economic activities happening on the downstream part of the river